Structural and spectroscopic properties of the peroxodiferric intermediate of Ricinus communis soluble Δ9 desaturase - Srnec, Martin; Rokob, Tibor András; Schwartz, Jennifer K; Kwak, Yeonju; Rulíšek, Lubomír; Solomon, Edward I (Inorganic chemistry, 2012)
Large-scale quantum and molecular mechanical methods (QM/MM) and QM calculations were carried out on the soluble Δ(9) desaturase (Δ(9)D) to investigate various structural models of the spectroscopically defined peroxodiferric (P) intermediate. This allowed us to formulate a consistent mechanistic picture for the initial stages of the reaction mechanism of Δ(9)D, an important diferrous nonheme iron enzyme that cleaves the C-H bonds in alkane chains resulting in the highly specific insertion of double bonds. The methods (density functional theory (DFT), time-dependent DFT (TD-DFT), QM(DFT)/MM, and TD-DFT with electrostatic embedding) were benchmarked by demonstrating that the known spectroscopic effects and structural perturbation caused by substrate binding to diferrous Δ(9)D can be qualitatively reproduced. We show that structural models whose spectroscopic (absorption, circular dichroism (CD), vibrational and Mössbauer) characteristics correlate best with experimental data for the P intermediate correspond to the μ-1,2-O(2)(2-) binding mode. Coordination of Glu196 to one of the iron centers (Fe(B)) is demonstrated to be flexible, with the monodentate binding providing better agreement with spectroscopic data, and the bidentate structure being slightly favored energetically (1-10 kJ mol(-1)). Further possible structures, containing an additional proton or water molecule are also evaluated in connection with the possible activation of the P intermediate. Specifically, we suggest that protonation of the peroxide moiety, possibly preceded by water binding in the Fe(A) coordination sphere, could be responsible for the conversion of the P intermediate in Δ(9)D into a form capable of hydrogen abstraction. Finally, results are compared with recent findings on the related ribonucleotide reductase and toluene/methane monooxygenase enzymes.
Keywords: desaturasy mastných kyselin; Models, Molecular; voda; molekulární modely; isomerie; Water; Peroxides; Isomerism; katalytická doména; Catalytic Domain; peroxidy; Fatty Acid Desaturases; Ricinus; Quantum Theory; spektroskopie Mossbauerova; Spectroscopy, Mossbauer; kvantová teorie